2019
DOI: 10.3390/e21100934
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale Approximate Entropy for Gait Analysis in Patients with Neurodegenerative Diseases

Abstract: Neurodegenerative diseases such as amyotrophic lateral sclerosis (ALS), Parkinson’s diseases (PD), and Huntington’s disease (HD) are not rare neurological diseases. They affect different neurological systems and present various characteristic gait abnormalities. We retrieved gait signals of the right and left feet from a public domain on the Physionet. There were 13 patients with ALS, 15 patients with PD, 20 patients with HD and 16 healthy controls (HC). We used multiscale approximate entropy (MAE) to analyze … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…The sensors used to measure vertical ground reaction force were placed inside a shoe insole with eight sensors on each foot, as shown in Figure 1. The sensors were made by Ultraflex Computer Dyno Graphy, Infotronic Inc. [19], and they recorded changes in force at a sampling rate of 100 Hz [20]. The highest frequency, feasible for analysis was set by the sampling rate at which the data were collected.…”
Section: Data Acquisition and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The sensors used to measure vertical ground reaction force were placed inside a shoe insole with eight sensors on each foot, as shown in Figure 1. The sensors were made by Ultraflex Computer Dyno Graphy, Infotronic Inc. [19], and they recorded changes in force at a sampling rate of 100 Hz [20]. The highest frequency, feasible for analysis was set by the sampling rate at which the data were collected.…”
Section: Data Acquisition and Analysismentioning
confidence: 99%
“…y is a set of data divided into nonoverlapping frames of length τ, where τ represents the scale factor and takes integer values equal to or greater than 1, which can be found using Equation (2). Therefore, τ is defined by length of N of X N and m. For example, N = 10,000 and m = 2, take 500 as the median of [10 m , 30 m ] [27], which is selected to calculate τ max = 10,000/500 = 20 and τ ∈ [1,20]. By using different scales, further data analysis can be made and more information about the gait patterns can be extracted.…”
Section: Sample Entropy and Multiscale Entropy Analysismentioning
confidence: 99%
“…Multiscale approximate entropy was calculated from the vGRF of both feet to the diagnosis and long-term assessment of NDDs. 143 Sample entropy was determined for the stride time, with vector length and threshold parameters optimized PD, and it found that PD patients had higher sample entropy stride time than older adults, indicating reduced gait regularity. 144 Sigmoid entropy of EEG signal was found to be better and computationally efficient when compared to other entropy methods.…”
Section: Resultsmentioning
confidence: 99%
“…This metric has been shown in previous studies to be useful for sleep-related and other neurological disorders. Approximate entropy has been shown to detect and characterize seizures in patients with epilepsy [17], classify neurodegenerative disorders from healthy controls [18], detect sleep hypopnea [19] and evaluate sleep quality in obstructive sleep apneahypopnea syndrome [20]. Recently, approximate entropy was also used in a nonlinear model combined with polysomnography (PSG) features like nasal airflow and thoracic movements to predict the presence and severity of OSA [21].…”
Section: Introductionmentioning
confidence: 99%